2004
DOI: 10.3168/jds.s0022-0302(04)73524-9
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Generation and Stability of the Lactokinin β-Lactoglobulin Fragment (142–148)

Abstract: The objectives of this study were to investigate the generation of beta-lactoglobulin fragment (142-148) (beta-LG f(142-148) during the hydrolysis of whey proteins, and the in vitro stability of this fragment upon incubation with gastrointestinal and serum proteinases and peptidases. An enzyme immunoassay (EIA) protocol was developed for the quantification of beta-LG f(142-148) in whey protein hydrolysates and in human blood serum. The minimum detection limit was 3 ng/mL. The level of the peptide in whey prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 32 publications
2
69
0
Order By: Relevance
“…Similarly, lactokinin (ALPMHIR) was found to inhibit the release of ET-1, an endothelial peptide that evokes contractions in smooth muscle cells, an effect that might be dependent or independent of ACE inhibition (Maes et al, 2004). However, when interpreting this result, the susceptibility of ALPMHIR to degradation by gastrointestinal, brush-border and serum proteinases and the ACE inhibitory activity of its degradation products, should be taken into account (Murakami et al, 2004;Walsh et al, 2004).…”
Section: Other Possible Mechanisms Of Actionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, lactokinin (ALPMHIR) was found to inhibit the release of ET-1, an endothelial peptide that evokes contractions in smooth muscle cells, an effect that might be dependent or independent of ACE inhibition (Maes et al, 2004). However, when interpreting this result, the susceptibility of ALPMHIR to degradation by gastrointestinal, brush-border and serum proteinases and the ACE inhibitory activity of its degradation products, should be taken into account (Murakami et al, 2004;Walsh et al, 2004).…”
Section: Other Possible Mechanisms Of Actionmentioning
confidence: 80%
“…Thus, the active ACE-inhibitory peptide lactokinin, ALPMHIR, that arises from tryptic hydrolysis of b-lactoglobulin (b-Lg f142-148, IC 50 ¼ 42.6 mM), was reported to be resistant to further hydrolysis by pepsin or chymotrypsin (Mullally, Meisel, & FitzGerald, 1997a). However, subsequent experiments revealed that ALPM-HIR was susceptible to degradation on incubation with gastrointestinal and blood serum proteinases and peptidases in vitro, what restricts its potential to elicit a hypotensive response in humans (Roufik et al, 2006;Walsh et al, 2004). Interestingly, the shorter fragment ALPM exerted a strong hypotensive effect in SHR despite the fact it was not an efficient ACE inhibitor in vitro (IC 50 ¼ 928 mM; Murakami et al, 2004).…”
Section: Bioavailability and Physiological Relevancementioning
confidence: 95%
“…Furthermore, a dose-dependent antihypertensive effect has been established in animal model studies with SHR after single oral administration of small di-and tripeptides . On the other hand, recent in vitro results by Walsh et al (2004) indicated that b-lg f(142-148), the tryptic peptide Ala-Leu-Pro-Met-His-Ile-Arg which is known to be a potent inhibitor of ACE activity in vitro (Mullally, Meisel, & FitzGerald, 1997) is probably not sufficiently stable to gastrointestinal and serum proteinases and peptidases to act as an hypotensive agent in humans following oral ingestion. This conclusion was supported by the results showing that synthetic b-lg f(142-148) was rapidly degraded upon incubation with human serum.…”
Section: Regulation Of the Cardiovascular Systemmentioning
confidence: 93%
“…They can be produced naturally during gastrointestinal (GI) digestion by the hydrolytic action of the proteinases pepsin, trypsin, chymotrypsin and by brush border peptidases [18]. Simulated GI digestion has been carried out on a range of protein sources to assess the effect of GI digestion on ACEinhibitory peptides [19][20][21][22][23][24]. More commonly, ACE-inhibitory peptides are produced through enzymatic hydrolysis with GI enzymes such as pepsin and trypsin or with enzyme combinations such as Alcalase™ [25].…”
Section: Hypotensive Mechanisms Of Actionmentioning
confidence: 99%